Acid Catalyzed Multicomponent One-Pot Synthesis of New Quinazolinone based Unsymmetrical C-N Linked Bis Heterocycles - Rayala, Nagamani; Vodnala, Sumathi; Kamsani, Supriya; Bhavani, A.K.D.; Myakala, Nagaraju; Kandula, Kotaiah; Mudiganti, Sucheta (Asian Journal of Chemistry, 2022)
A novel series of unsymmetrical C-N linked bis heterocycles bearing quinazolinone and acridinedione skeletons have been synthesized in an acid promoted one pot multicomponent reaction. A blend of 6-aminoquinazolin-4-(3H)-one, aromatic aldehydes and cyclohexane-1,3-dione in a simple and efficient condensation-cyclization reaction using hydrochloric acid in catalytic amount as catalyst afforded unsymmetrical bis hybrids in good to excellent yields. Multiheterocyclic hybrid compounds were also synthesized using heterocyclic ring containing aldehyde in three component reaction. The synthesized quinazolinone-acridindione hybrids were characterized using spectroscopic techniques such as a IR, 1H NMR, 13C NMR, ESI-mass and HRMS.